Method for improving saline-alkaline tolerance of corn seeds by using organic silicon

The corn seeds are coated with composite solutions of silicone, modified nano-hydroxyapatite and carboxymethylcellulose to form a protective film, which solves the problem of soil salinization on corn seeds and improves the salinity and alkali resistance of the seeds and the germination index have achieved economical and efficient improvement in agricultural production efficiency.

CN119138145AInactive Publication Date: 2024-12-17INST OF SOIL FERTILIZER & WATER SAVING AGRI GANSU ACAD OF AGRI SCI

Patent Information

Application Number
CN202411639344.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Soil salinization causes damage to corn seeds, reducing germination rate and nutrient absorption, and the existing improvement costs are high and the cycle is long, and there is a lack of economically feasible methods to improve the salinity and alkali tolerance of corn seeds.

Method used

Coated corn seeds with a composite solution of silicone and modified nanohydroxyapatite and carboxymethylcellulose, and form a protective film through chemical bonds and physical cross-linking, enhancing the mechanical strength of the cell wall, reducing harmful ion absorption, regulating the moisture environment, and improving Seed germination ability.

Benefits of technology

Significantly improve the saline-alkali tolerance of corn seeds, improve germination rate and germination index, reduce the impact of saline-alkali stress on seeds, and has low treatment costs and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119138145A_ABST
    Figure CN119138145A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of agricultural planting, in particular to a method for improving saline-alkaline tolerance of corn seeds by using organic silicon, which comprises the steps of seed pretreatment, pre-soaking, seed dressing, drying, after-ripening and the like. The organic silicon forms a firm chemical bonding interface on the surface of the seed, a protective film is formed through a Si-O-Si network structure, the modified nano-hydroxyapatite further promotes the formation of the protective film through physical crosslinking and chemical bonding effects, and the mechanical strength of the cell wall of the seed is further enhanced through nano-filling; the absorption of seed cells to harmful ions such as Na < + > and Cl <-> is continuously reduced, the carboxymethyl cellulose effectively prevents organosilicon molecules from approaching the modified nano-hydroxyapatite through a steric hindrance effect, the structural and functional integrity of the organosilicon molecules and the modified nano-hydroxyapatite is ensured, and the extremely strong water absorption and water retention performance of the carboxymethyl cellulose continuously relieves the influence of osmotic stress on seed germination; the organic silicon molecules and the modified nano-hydroxyapatite are cooperated to improve the saline-alkaline tolerance of the corn seeds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of agricultural planting, and in particular to a method for improving the salt-alkali resistance of corn seeds by utilizing organic silicon. Background Art

[0002] There are many reasons for soil salinization, including natural factors such as climate and topography, but the main reason is human factors, such as unreasonable irrigation and excessive use of fertilizers. If the soil is seriously salinized, then salinity stress will have many adverse effects on corn seeds. The high salt environment will reduce the soil water potential, making it difficult for corn seeds to absorb water, resulting in a decrease in germination rate; if Na⁺, Cl⁻ and other ions accumulate excessively, these ions will further poison corn seeds and destroy the seed cell structure; at the same time, excessive Na⁺ will also affect the absorption of other ions, especially K⁺, leading to nutritional imbalance; oxidative stress will further induce excessive reactive oxygen and damage the seed cell membrane system. Due to the high cost and long cycle of saline-alkali land improvement, improving the salt-alkali tolerance of cash crops is an economically feasible method, and silicone has good physiological activity, which can significantly improve plant stress resistance, is safe and environmentally friendly, and also meets the requirements of sustainable development. Organic silicon can enhance the mechanical strength of seed cell walls, improve stress resistance, improve ion balance, reduce excessive accumulation of Na⁺ and Cl⁻, increase antioxidant enzyme activity, remove excessive reactive oxygen, promote the synthesis of osmotic regulating substances, maintain cell osmotic balance, regulate plant hormone levels, and promote seed germination and seedling growth. At the same time, it is easy to use and can be treated by seed coating, seed soaking, etc.; it is effective quickly, and salt tolerance can be improved in a short period of time after organic silicon treatment; organic silicon has low cost, small dosage, good economic benefits; it is environmentally friendly and will not cause secondary pollution. Summary of the invention

[0003] (1) Technical issues to be resolved The purpose of the present invention is to provide a method for improving the salt-alkali tolerance of corn seeds by using organosilicon, so as to effectively improve the salt-alkali tolerance of corn seeds, cope with the challenges brought by soil salinization, and improve agricultural production efficiency.

[0004] (2) Technical solution To achieve the above object, the present invention provides a method for improving the salt-alkali tolerance of corn seeds by using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water 2-3 times, and then disinfect them with 75% alcohol for 30-60 seconds; S12. Pre-soaking: Soak the pre-treated corn seeds in purified water for 2-4 hours, stirring gently every 30 minutes. The volume ratio of corn seeds to purified water is 1:(1.5-2). After soaking, drain the moisture on the surface of the seeds. S13. Seed dressing: Place the pre-soaked corn seeds in a cantilever coating machine and spray the organosilicon composite solution by atomization. The mass ratio of corn seeds to organosilicon composite solution is 100:(1.5~3). The organosilicon composite solution is evenly added in 2~3 times. The speed is controlled at 150~200rpm, the blast temperature is 25~28℃, and the treatment time is 8~10min. S14. Drying: Place the corn seeds treated with seed dressing in an electric constant temperature air drying oven, set the air temperature to 25-30°C, treat for 1-1.5 hours, then take out and air dry naturally for 2-3 hours; S15. Post-ripening: Naturally pile the dried corn seeds at an ambient temperature of 20-25°C and use a light-shielding bag to avoid strong light exposure. After standing for 12-15 hours, store the obtained corn seeds away from light; The preparation method of the organosilicon composite solution comprises: S21. Slowly add carboxymethyl cellulose to purified water under stirring, set the heating temperature to 80-95°C, the stirring speed to 300-400 rpm, and stir for 0.5-1 h to obtain a carboxymethyl cellulose solution; S22. The modified nano-hydroxyapatite was slowly added to the carboxymethyl cellulose solution under stirring, and ultrasonic treatment was performed after stirring for 0.5 to 1 h. The intermittent mode was set to work for 2 min and stop for 1 min. The ultrasonic frequency was 40 to 50 kHz. The first mixed solution was obtained after ultrasonic treatment at room temperature for 0.5 to 1 h. S23. Slowly add the organosilicon solution to the first mixed solution under stirring, set the stirring temperature to 30-35°C, the stirring speed to 400-500 rpm, stir for 1-2 hours, transfer to a high-pressure homogenizer, set the pressure to 30-40 MPa, cycle 2-3 times, and filter through a 0.22 μm filter membrane to obtain an organosilicon composite solution.

[0005] Furthermore, the organic silicon solution is a compound of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane, and the weight ratio of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and vinyltriethoxysilane is (20-25): (15-18): (10-12).

[0006] Furthermore, the carboxymethyl cellulose, modified nano-hydroxyapatite and organosilicon solution are in a weight ratio of (10-15):(2-4):(1-2).

[0007] Furthermore, the preparation method of the modified nano-hydroxyapatite comprises: S31. Dispersing hydroxyapatite in purified water under stirring, slowly adding acrylic acid monomer after stirring for 0.5 to 1 hour, continuing stirring for 1 to 2 hours, and then ultrasonically treating, setting an intermittent mode, working for 2 minutes, stopping for 1 minute, ultrasonic frequency of 40 to 50 kHz, ultrasonically treating at room temperature for 0.5 to 1 hour to obtain a second mixed solution; S32. Under nitrogen protection, the ammonium persulfate solution was added to the second mixed solution, the temperature was raised to 65-75°C, and the reaction was stirred for 4-6 hours to obtain a third mixed solution; S33. The third mixed solution is subjected to high-speed centrifugation at a rotation speed of 10000-12000 rpm for 10-15 min. The separated solid is washed alternately with purified water and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 50-60° C. After drying for 12-14 h, the modified nano-hydroxyapatite is obtained and ground into powder for later use.

[0008] Furthermore, the modified nano-hydroxyapatite is obtained by grafting polyacrylic acid on the surface of hydroxyapatite and nano-crystallizing the surface of the hydroxyapatite, and the particle size of the modified nano-hydroxyapatite is 45-60 nm and the specific surface area is 180-225 m 2 / g.

[0009] Furthermore, the mass ratio of the hydroxyapatite, acrylic acid monomer and ammonium persulfate solution is 1:(2-4):(0.2-0.4).

[0010] The mechanism of action of the above raw material components is as follows: In the method of using organosilicon to improve the salt-alkali tolerance of corn seeds, organosilicon molecules such as γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane react with the active groups on the surface of the seeds to form a strong chemical bonding interface. At the same time, the silanol group (Si-OH) further condenses to form a Si-O-Si network structure, and then forms a protective film, thereby enhancing the mechanical strength of the seed cell wall. The modified nano-hydroxyapatite with polyacrylic acid grafted on the surface further promotes the formation of the protective film through physical cross-linking and chemical bonding, and continuously reduces the seed cells' sensitivity to Na + , Cl - The introduction of polyacrylic acid improves the dispersibility of modified nano-hydroxyapatite, and nano-filling further enhances the mechanical strength of the seed cell wall, while also providing Ca for the seeds. 2+ and PO4 3-The presence of carboxymethyl cellulose weakens the physical adsorption of organosilicon and modified nano-hydroxyapatite, which will lead to a decrease in the specific surface area of ​​modified nano-hydroxyapatite, thereby affecting the release of Ca by modified nano-hydroxyapatite. 2+ and PO4 3- Nutrients such as hydroxyapatite and carboxymethyl cellulose can effectively prevent organic silicon molecules from approaching modified nano-hydroxyapatite through steric hindrance, ensuring the structural and functional integrity of both. At the same time, carboxymethyl cellulose has extremely strong water absorption and water retention properties, and can still maintain suitable moisture conditions under saline-alkali stress. By adjusting the moisture environment around the seeds, it can continuously alleviate the effects of osmotic stress on seed germination, and synergize with organic silicon molecules and modified nano-hydroxyapatite to improve the salt-alkali resistance of corn seeds. In addition, organic silicon molecules, modified nano-hydroxyapatite and carboxymethyl cellulose all have good biocompatibility, have a positive effect on the ventilation and water retention of saline-alkali soils, and have good environmental compatibility.

[0011] (3) Beneficial effects Compared with the prior art, the present invention has the following beneficial effects: 1. Organic silicon reacts with the active groups on the surface of seeds to form a strong chemical bonding interface. The silanol groups further condense to form a Si-O-Si network structure, which in turn forms a protective film and enhances the mechanical strength of the seed cell wall. 2. Modified nano-hydroxyapatite further promotes the formation of protective film through physical cross-linking and chemical bonding, and continuously reduces the sensitivity of seed cells to Na + , Cl - The absorption of harmful ions such as iodine and iodine can be reduced, and the mechanical strength of the seed cell wall can be further enhanced by nanofilling; 3. Modified nanohydroxyapatite provides Ca for seeds 2+ and PO4 3- And other nutrients, promote cell wall synthesis, stabilize cell wall structure, promote seed germination and root development; 4. Carboxymethyl cellulose effectively prevents silicone molecules from approaching modified nano-hydroxyapatite through steric hindrance, weakens its physical adsorption effect, and ensures the integrity of the structure and function of both; 5. The strong water absorption and water retention properties of carboxymethyl cellulose enable it to maintain suitable moisture conditions under saline-alkali stress, continuously alleviate the impact of osmotic stress on seed germination, and synergize with silicone molecules and modified nano-hydroxyapatite to enhance the salt-alkali resistance of corn seeds. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is the SEM image of the modified nano-hydroxyapatite in Example 1 of the present invention. DETAILED DESCRIPTION

[0013] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] The experimental equipment and preparations of the embodiments described below are as follows: electronic balance (Sartorius, Germany), electric constant temperature water bath (Jiangsu Kedao), magnetic stirrer (Shanghai Meiyingpu), ultrasonic instrument (Shanghai Yixin), high-speed centrifuge (Guangzhou Jidi), vacuum homogenizer (Shanghai Noze), rotary evaporator (Shanghai Yaote), constant temperature incubator (Shanghai Zhulan), scanning electron microscope (Zeiss, Germany), specific surface area analyzer (Beijing Best Instrument Technology); chemicals and reagents were purchased from Sigma-Aldrich.

[0015] Example 1: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 45 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 3 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13. Seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:2. The silicone composite solution was evenly added in 3 portions. The speed was controlled at 200 rpm, the blast temperature was 25 ° C, and the treatment time was 10 min. S14. Drying: Place the corn seeds treated with seed dressing in an electric constant temperature blast drying oven, set the blast temperature to 28°C, take out after the treatment time of 1.5h and dry naturally for 2.5h; S15. Ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and placed in a light-shielding bag to avoid strong light exposure. The corn seeds were stored in a dark place after standing for 14 hours; The preparation method of the organosilicon composite solution comprises: S21. The carboxymethyl cellulose was slowly added to the purified water under stirring, the heating temperature was set to 90 ° C, the stirring speed was 350 rpm, and the carboxymethyl cellulose solution was obtained after stirring for 1 h; S22. The modified nano-hydroxyapatite was slowly added to the carboxymethyl cellulose solution under stirring, and then ultrasonically treated for 1 hour. The intermittent mode was set to work for 2 minutes, stop for 1 minute, and the ultrasonic frequency was 45 kHz. After ultrasonic treatment at room temperature for 1 hour, a first mixed solution was obtained; S23. Slowly add the organosilicon solution to the first mixed solution under stirring, set the stirring temperature to 35°C, the stirring speed to 450rpm, and transfer to a high-pressure homogenizer after stirring for 1.5h, set the pressure to 35 MPa, and after three cycles, filter through a 0.22μm filter membrane to obtain an organosilicon composite solution.

[0016] The organic silicon solution is a compound of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane, and the weight ratio of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane is 22:16:11.

[0017] The carboxymethyl cellulose, modified nano-hydroxyapatite and organic silicon solution are present in a weight ratio of 12:3:2.

[0018] The preparation method of the modified nano-hydroxyapatite comprises: S31. The hydroxyapatite was dispersed in purified water under stirring, and the acrylic acid monomer was slowly added after stirring for 1 hour. After stirring for 2 hours, ultrasonic treatment was performed, and an intermittent mode was set, working for 2 minutes, stopping for 1 minute, and the ultrasonic frequency was 45 kHz. After ultrasonic treatment at room temperature for 1 hour, a second mixed solution was obtained; S32. Under nitrogen protection, the ammonium persulfate solution was added to the second mixed solution, the temperature was raised to 70 ° C, and the reaction was stirred for 5 hours to obtain a third mixed solution; S33. The third mixed solution was subjected to high-speed centrifugation at a speed of 11000 rpm for 15 min. The separated solid was washed alternately with purified water and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 55° C. After drying for 13 h, the modified nano-hydroxyapatite was obtained and ground into powder for later use.

[0019] The modified nano-hydroxyapatite is obtained by grafting polyacrylic acid on the surface of hydroxyapatite and nano-crystallizing the surface of the hydroxyapatite. The particle size of the modified nano-hydroxyapatite is 55 nm and the specific surface area is 220 m 2 / g.

[0020] The mass ratio of the hydroxyapatite, acrylic acid monomer and ammonium persulfate solution is 1:3:0.3.

[0021] In the method of using organosilicon to improve the salt-alkali tolerance of corn seeds, the epidermal cells of corn seeds after pre-soaking treatment contain abundant active groups such as hydroxyl (-OH), amino (-NH2), carboxyl (-COOH) and thiol (-SH), and the surfaces of organosilicon molecules such as γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane contain abundant alkoxy groups (Si-OR) that can be hydrolyzed to generate silanol groups (Si-OH). The hydrolyzed silanol groups (Si-OH) further form Si-ON bonds with amino groups (-NH2) of seed epidermal cells and Si-OC bonds with hydroxyl groups (-OH) to form a strong chemical bonding interface. At the same time, the silanol groups (Si-OH) further condense to form a Si-O-Si network structure, thereby forming a protective film and enhancing the mechanical strength of the seed cell wall. The modified nano-hydroxyapatite grafted with polyacrylic acid further promotes the formation of the protective film through physical crosslinking and chemical bonding. Figure 1 As shown in the SEM image of modified nano-hydroxyapatite, the modified nano-hydroxyapatite has uniform particle size and spherical morphology, has a large specific surface area and high surface activity, and is rich in hydroxyl (-OH) and phosphate (PO4 3- ) and carboxyl (-COOH), which can further promote the crosslinking and entanglement of the network structure through physical crosslinking effects such as intermolecular hydrogen bonds, van der Waals forces and electrostatic interactions. At the same time, the polyacrylic acid grafted on the surface of modified nanohydroxyapatite contains abundant carboxyl groups (-COOH). Its introduction not only improves the dispersibility of modified nanohydroxyapatite, but also undergoes condensation reaction with the silane group (Si-OR) on the surface of the organosilicon molecule, esterification reaction with the silanol group (Si-OH), and esterification reaction with the hydroxyl group (-OH) on the seed surface, and further promotes the formation of a covalent network structure through the bridging effect of calcium ions. Nanoparticle filling also further enhances the mechanical strength of the seed cell wall. The protective film formed by the organosilicon molecules and modified nanohydroxyapatite can effectively reduce Na + , Cl - The transmembrane transport of harmful ions such as Na + , Cl - It also provides Ca for the seeds. 2+ and PO4 3- It can promote cell wall synthesis, stabilize cell wall structure, and promote seed germination and root development. Since the modified nano-hydroxyapatite has a large specific surface area, it has a certain physical adsorption effect on the organosilicon molecules. This physical adsorption makes the adsorption active sites of the modified nano-hydroxyapatite occupied by the organosilicon molecules, resulting in a decrease in the specific surface area of ​​the modified nano-hydroxyapatite, thereby affecting the release of Ca by the modified nano-hydroxyapatite. 2+ and PO4 3-The presence of carboxymethyl cellulose can effectively weaken the physical adsorption of the two. The macromolecular chain of carboxymethyl cellulose forms a three-dimensional barrier through the steric hindrance effect, which can effectively prevent the organosilicon molecules from approaching the modified nano-hydroxyapatite, ensuring the integrity of the structure and function of the two. At the same time, carboxymethyl cellulose has extremely strong water absorption and water retention properties. It can still maintain suitable water conditions under saline-alkali stress, and maintain the normal turgor pressure of seed cells by adjusting the water environment around the seeds, continuously alleviating the effect of osmotic stress on seed germination, ensuring the water required for seed germination, and synergizing with organosilicon molecules and modified nano-hydroxyapatite to improve the salt-alkali resistance of corn seeds. In addition, organosilicon molecules, modified nano-hydroxyapatite and carboxymethyl cellulose have good biocompatibility, have a positive effect on the ventilation and water retention of saline-alkali soils, and have good environmental compatibility.

[0022] Example 2: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them twice with clean water, and then disinfect them with 75% alcohol for 30 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 2 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:1.5, and drain the surface water of the seeds after soaking; S13. Seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:2. The silicone composite solution was evenly added in 2 times. The speed was controlled at 150 rpm, the blast temperature was 25 ° C, and the treatment time was 8 min. S14. Drying: Place the corn seeds treated with the dressing in an electric constant temperature blast drying oven, set the blast temperature to 25°C, take out after the treatment time of 1 hour and air dry naturally for 2 hours; S15. Ripening: The dried corn seeds were naturally piled up at an ambient temperature of 20°C and placed in a light-shielding bag to avoid strong light exposure. The corn seeds were stored in a dark place after standing for 12 hours; The preparation method of the organosilicon composite solution comprises: S21. The carboxymethyl cellulose was slowly added to the purified water under stirring, the heating temperature was set to 80 ° C, the stirring speed was 300 rpm, and the carboxymethyl cellulose solution was obtained after stirring for 0.5 h; S22. The modified nano-hydroxyapatite was slowly added to the carboxymethyl cellulose solution under stirring, and ultrasonic treatment was performed after stirring for 0.5 h. The intermittent mode was set to work for 2 min, stop for 1 min, and the ultrasonic frequency was 40 kHz. After ultrasonic treatment at room temperature for 0.5 h, a first mixed solution was obtained; S23. Slowly add the organosilicon solution to the first mixed solution under stirring, set the stirring temperature to 30°C, the stirring speed to 400 rpm, and after stirring for 1 hour, transfer to a high-pressure homogenizer and set the pressure to 30 MPa. After two cycles, filter through a 0.22 μm filter membrane to obtain an organosilicon composite solution.

[0023] The organic silicon solution is a compound of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane, and the weight ratio of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane is 22:16:11.

[0024] The carboxymethyl cellulose, modified nano-hydroxyapatite and organic silicon solution are present in a weight ratio of 12:3:2.

[0025] The preparation method of the modified nano-hydroxyapatite comprises: S31. The hydroxyapatite was dispersed in purified water under stirring, and the acrylic acid monomer was slowly added after stirring for 0.5 h. After stirring for 1 h, ultrasonic treatment was performed, and an intermittent mode was set, working for 2 min, stopping for 1 min, and the ultrasonic frequency was 40 kHz. After ultrasonic treatment at room temperature for 0.5 h, a second mixed solution was obtained; S32. Under nitrogen protection, the ammonium persulfate solution was added to the second mixed solution, the temperature was raised to 65 ° C, and the reaction was stirred for 4 hours to obtain a third mixed solution; S33. The third mixed solution was subjected to high-speed centrifugation at a speed of 10,000 rpm for 10 min. The separated solid was washed alternately with purified water and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 50° C. After drying for 12 h, the modified nano-hydroxyapatite was obtained and ground into powder for later use.

[0026] The modified nano-hydroxyapatite is obtained by grafting polyacrylic acid on the surface of hydroxyapatite and nano-crystallizing the surface of the hydroxyapatite. The particle size of the modified nano-hydroxyapatite is 45 nm and the specific surface area is 200 m 2 / g.

[0027] The mass ratio of the hydroxyapatite, acrylic acid monomer and ammonium persulfate solution is 1:2:0.2.

[0028] Example 3: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 60 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 4 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13. Seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:2. The silicone composite solution was evenly added in 3 portions. The speed was controlled at 200 rpm, the blast temperature was 28 ° C, and the treatment time was 10 min. S14. Drying: Place the corn seeds treated with the dressing in an electric constant temperature blast drying oven, set the blast temperature to 30°C, take out after the treatment time of 1.5h and dry naturally for 3h; S15. Ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and placed in a light-shielding bag to avoid strong light exposure. The corn seeds were stored in a dark place after standing for 15 hours; The preparation method of the organosilicon composite solution comprises: S21. The carboxymethyl cellulose was slowly added to the purified water under stirring, the heating temperature was set to 95 ° C, the stirring speed was 400 rpm, and the carboxymethyl cellulose solution was obtained after stirring for 1 h; S22. The modified nano-hydroxyapatite was slowly added to the carboxymethyl cellulose solution under stirring, and then ultrasonically treated for 1 hour. The intermittent mode was set to work for 2 minutes, stop for 1 minute, and the ultrasonic frequency was 50 kHz. After ultrasonic treatment at room temperature for 1 hour, a first mixed solution was obtained; S23. Slowly add the organosilicon solution to the first mixed solution under stirring, set the stirring temperature to 35°C, the stirring speed to 500 rpm, and transfer to a high-pressure homogenizer after stirring for 2 hours, set the pressure to 40 MPa, and after three cycles, filter through a 0.22 μm filter membrane to obtain an organosilicon composite solution.

[0029] The organic silicon solution is a compound of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane, and the weight ratio of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane is 22:16:11.

[0030] The carboxymethyl cellulose, modified nano-hydroxyapatite and organic silicon solution are present in a weight ratio of 12:3:2.

[0031] The preparation method of the modified nano-hydroxyapatite comprises: S31. The hydroxyapatite was dispersed in purified water under stirring, and the acrylic acid monomer was slowly added after stirring for 1 h. After stirring for 2 h, ultrasonic treatment was performed, and an intermittent mode was set, working for 2 min, stopping for 1 min, and the ultrasonic frequency was 50 kHz. After ultrasonic treatment at room temperature for 1 h, a second mixed solution was obtained; S32. Under nitrogen protection, the ammonium persulfate solution was added to the second mixed solution, the temperature was raised to 75 ° C, and the reaction was stirred for 6 hours to obtain a third mixed solution; S33. The third mixed solution was subjected to high-speed centrifugation at a speed of 12,000 rpm for 15 minutes. The separated solid was washed alternately with purified water and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 60° C. After drying for 14 hours, the modified nano-hydroxyapatite was obtained and ground into powder for later use.

[0032] The modified nano-hydroxyapatite is obtained by grafting polyacrylic acid on the surface of hydroxyapatite and nano-crystallizing the surface of the hydroxyapatite. The particle size of the modified nano-hydroxyapatite is 60 nm and the specific surface area is 185 m 2 / g.

[0033] The mass ratio of the hydroxyapatite, acrylic acid monomer and ammonium persulfate solution is 1:4:0.4.

[0034] Example 4: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 45 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 3 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13 seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:1.5. The silicone composite solution was evenly added in 3 portions. The speed was controlled at 200 rpm, the blast temperature was 25 ° C, and the treatment time was 10 min. S14. Drying: Place the corn seeds treated with seed dressing in an electric constant temperature blast drying oven, set the blast temperature to 28°C, take out after the treatment time of 1.5h and dry naturally for 2.5h; S15. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and covered with light-shielding bags to avoid strong light exposure. After standing for 14 hours, the corn seeds were stored away from light.

[0035] The preparation method of the organosilicon composite solution and modified nano-hydroxyapatite in this embodiment is consistent with that in Example 1.

[0036] Example 5: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them twice with clean water, and then disinfect them with 75% alcohol for 30 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 2 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:1.5, and drain the surface water of the seeds after soaking; S13. Seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:1.5. The silicone composite solution was evenly added in 2 times. The speed was controlled to 150 rpm, the blast temperature was 25 ° C, and the treatment time was 8 min. S14. Drying: Place the corn seeds treated with the dressing in an electric constant temperature blast drying oven, set the blast temperature to 25°C, take out after the treatment time of 1 hour and air dry naturally for 2 hours; S15. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 20°C and protected from strong light by using light-shielding bags. The corn seeds were left to stand for 12 hours and then stored away from light.

[0037] The preparation method of the organosilicon composite solution and modified nano-hydroxyapatite in this embodiment is consistent with that in Example 2.

[0038] Example 6: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 60 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 4 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13 seed dressing: the pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:1.5. The silicone composite solution was evenly added in 3 times, the speed was controlled at 200 rpm, the blast temperature was 28 ° C, and the treatment time was 10 min; S14. Drying: Place the corn seeds treated with the dressing in an electric constant temperature blast drying oven, set the blast temperature to 30°C, take out after the treatment time of 1.5h and dry naturally for 3h; S15. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and protected from strong light by using light-shielding bags. The corn seeds were left to stand for 15 hours and then stored away from light.

[0039] The preparation method of the organosilicon composite solution and modified nano-hydroxyapatite in this embodiment is consistent with that in Example 3.

[0040] Example 7: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 45 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 3 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13 seed dressing: the pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:3. The silicone composite solution was evenly added in 3 times. The speed was controlled at 200 rpm, the blast temperature was 25 ° C, and the treatment time was 10 min. S14. Drying: Place the corn seeds treated with seed dressing in an electric constant temperature blast drying oven, set the blast temperature to 28°C, take out after the treatment time of 1.5h and dry naturally for 2.5h; S15. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and covered with light-shielding bags to avoid strong light exposure. After standing for 14 hours, the corn seeds were stored away from light.

[0041] The preparation method of the organosilicon composite solution and modified nano-hydroxyapatite in this embodiment is consistent with that in Example 1.

[0042] Example 8: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them twice with clean water, and then disinfect them with 75% alcohol for 30 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 2 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:1.5, and drain the surface water of the seeds after soaking; S13. Seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine, and the organosilicon composite solution was sprayed by atomization. The mass ratio of corn seeds to the organosilicon composite solution was 100:3. The organosilicon composite solution was evenly added in 2 portions. The speed was controlled at 150 rpm, the blast temperature was 25 ° C, and the treatment time was 8 min. S14. Drying: Place the corn seeds treated with the dressing in an electric constant temperature blast drying oven, set the blast temperature to 25°C, take out after the treatment time of 1 hour and air dry naturally for 2 hours; S15. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 20°C and protected from strong light by using light-shielding bags. The corn seeds were left to stand for 12 hours and then stored away from light.

[0043] The preparation method of the organosilicon composite solution and modified nano-hydroxyapatite in this embodiment is consistent with that in Example 2.

[0044] Example 9: This example discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, comprising the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 60 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 4 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13. Seed dressing: The pre-soaked corn seeds were placed in a cantilever coating machine, and the silicone composite solution was sprayed by atomization. The mass ratio of corn seeds to the silicone composite solution was 100:3. The silicone composite solution was evenly added in 3 times. The speed was controlled at 200 rpm, the blast temperature was 28 ° C, and the treatment time was 10 min. S14. Drying: Place the corn seeds treated with the dressing in an electric constant temperature blast drying oven, set the blast temperature to 30°C, take out after the treatment time of 1.5h and dry naturally for 3h; S15. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and protected from strong light by using light-shielding bags. The corn seeds were left to stand for 15 hours and then stored away from light.

[0045] The preparation method of the organosilicon composite solution and modified nano-hydroxyapatite in this embodiment is consistent with that in Example 3.

[0046] Control group 1: The difference between this embodiment and embodiment 1 is that the organosilicon composite solution does not contain an organosilicon solution. This embodiment discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, and the preparation method of the organosilicon composite solution includes: S21. The carboxymethyl cellulose was slowly added to the purified water under stirring, the heating temperature was set to 90 ° C, the stirring speed was 350 rpm, and the carboxymethyl cellulose solution was obtained after stirring for 1 h; S22. The modified nano-hydroxyapatite was slowly added to the carboxymethyl cellulose solution under stirring, and then ultrasonically treated for 1 hour. The intermittent mode was set to work for 2 minutes, stop for 1 minute, and the ultrasonic frequency was 45 kHz. After ultrasonic treatment at room temperature for 1 hour, a first mixed solution was obtained; S23. The first mixed solution was transferred to a high-pressure homogenizer, the pressure was set to 35 MPa, and after three cycles, the mixed solution was filtered through a 0.22 μm filter membrane to obtain an organosilicon composite solution.

[0047] The preparation method of the modified nano-hydroxyapatite in this embodiment is consistent with that in Example 1. The method of improving the salt-alkali tolerance of corn seeds by using organosilicon in this embodiment is consistent with that in Example 1.

[0048] Control group 2: The difference between this embodiment and embodiment 1 is that the organosilicon composite solution does not contain carboxymethyl cellulose. This embodiment discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, and the preparation method of the organosilicon composite solution includes: S21. The modified nano-hydroxyapatite was slowly added to purified water under stirring, and ultrasonic treatment was performed after stirring for 1 hour. The intermittent mode was set to work for 2 minutes, stop for 1 minute, and the ultrasonic frequency was 45 kHz. After ultrasonic treatment at room temperature for 1 hour, a first mixed solution was obtained; S23. Slowly add the organosilicon solution to the first mixed solution under stirring, set the stirring temperature to 35°C, the stirring speed to 450rpm, and transfer to a high-pressure homogenizer after stirring for 1.5h, set the pressure to 35 MPa, and after three cycles, filter through a 0.22μm filter membrane to obtain an organosilicon composite solution.

[0049] The preparation method of the modified nano-hydroxyapatite in this embodiment is consistent with that in Example 1. The method of improving the salt-alkali tolerance of corn seeds by using organosilicon in this embodiment is consistent with that in Example 1.

[0050] Control group 3: The difference between this embodiment and embodiment 1 is that the organosilicon composite solution does not contain modified nano-hydroxyapatite. This embodiment discloses a method for improving the salt-alkali tolerance of corn seeds using organosilicon, and the preparation method of the organosilicon composite solution comprises: S21. The carboxymethyl cellulose was slowly added to the purified water under stirring, the heating temperature was set to 90 ° C, the stirring speed was 350 rpm, and the carboxymethyl cellulose solution was obtained after stirring for 1 h; S23. Slowly add the organosilicon solution to the carboxymethyl cellulose solution under stirring, set the stirring temperature to 35°C, the stirring speed to 450 rpm, and transfer to a high-pressure homogenizer after stirring for 1.5 hours, set the pressure to 35 MPa, and after three cycles, filter through a 0.22 μm filter membrane to obtain an organosilicon composite solution.

[0051] The method of using organosilicon to improve the salt-alkali tolerance of corn seeds in this embodiment is consistent with that in Example 1.

[0052] Blank group: This example differs from Example 1 in that it does not contain an organosilicon composite solution and includes the following steps: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water for 3 times, and then disinfect them with 75% alcohol for 45 seconds; S12. Pre-soaking: Soak the pretreated corn seeds in purified water for 3 hours, stirring gently every 30 minutes, the volume ratio of corn seeds to purified water is 1:2, and after soaking, drain the surface water of the seeds; S13 Drying: After the pre-soaking, the corn seeds were placed in an electric constant temperature blast drying oven, the blast temperature was set to 28°C, and the treatment time was 1.5h and then taken out for natural air drying for 2.5h; S14. Post-ripening: The dried corn seeds were naturally piled up at an ambient temperature of 25°C and covered with light-shielding bags to avoid strong light exposure. After standing for 14 hours, the corn seeds were stored away from light.

[0053] Effect evaluation: Preparation of NaCl solution: Use purified water to prepare NaCl solution with a total of 5 concentration gradients of 0, 50, 100, 150 and 200 mmol / L, and place in a ground-mouth bottle for later use.

[0054] Seed germination experiment: 39 culture dishes were prepared, double-layer filter paper was laid in the culture dishes, 100 mmol / L NaCl solution was added to fully moisten the filter paper, 150 corn seeds were randomly selected from each experimental group and placed in the culture dishes, 50 seeds were placed in each culture dish, 3 parallel groups were placed in a constant temperature incubator, the culture temperature was set to 25±1℃, the relative humidity was 85~90%, and the light and dark were alternately cultivated for 12h. The seeds were observed and water was added regularly every day, and the other conditions were kept the same. Referring to GB / T3543.4 "Inspection Procedures for Crop Seeds", the root length of 2mm was used as the germination standard. After 4 days of cultivation, the germination was recorded and observed regularly every day, and the number of germinated seeds was recorded every day until the 8th day. Seed germination rate (%) = (germination number / total number of grains) × 100%; germination potential (%) = (germination number in 4 days / total number of grains) × 100%; germination index (GI) = ∑ (Gt / Dt), Gt is the number of germinations on day t, and Dt is the corresponding number of germination days. The germination index of corn seeds in each experimental group was averaged and the test results were recorded.

[0055]

[0056] Table 1 shows the statistical results of corn seed growth in each experimental group on the 8th day under the stress of 100 mmol / L NaCl solution. The germination index can reflect the comprehensive vitality of seeds during the entire germination period. As can be seen from Table 1, the germination index of the corn seeds in the blank group is the lowest, which is obviously affected by the stress of Na⁺ and Cl⁻ ions. By comparing the germination of corn seeds in Example 1, Example 2 and Example 3, it can be found that the different preparation conditions of the organosilicon composite solution also have a certain effect on the germination of corn seeds. By comparing the germination of corn seeds in Example 1, Example 4 and Example 7 with the germination of corn seeds in the control groups 1 to 3, it can be found that the germination of corn seeds in Example 1, Example 4 and Example 7 is better than that in the control groups 1 to 3, among which the germination of corn seeds in Example 1 is the best. By the 8th day, the germination rate reaches 94.00%, the germination potential is 88.0%, and the germination index is 27.70%. By comparing Example 1 with the control groups 1 to 3, it can be found that when the organosilicon composite solution is prepared by using modified nano-hydroxyapatite, carboxymethyl cellulose and organosilicon solution and sprayed on corn seeds, the salt-alkali resistance of corn seeds can be effectively improved.

[0057] NaCl solution stress experiment: prepare 15 culture dishes, lay double-layer filter paper in the culture dishes, randomly select 750 corn seeds from Example 1 and put them into the culture dishes, with 50 seeds placed in each culture dish, and add 0, 50, 100, 150 and 200 mmol / L NaCl solutions in sequence to fully moisten the filter paper. Three parallel groups were placed in a constant temperature incubator, the culture temperature was set to 25±1°C, the relative humidity was 85-90%, and the light and dark were alternately cultured for 12 hours. The seeds were observed and water was supplemented regularly every day. The other conditions were kept consistent. The germination index of corn seeds in each experimental group was averaged and the measurement results were recorded.

[0058]

[0059] Table 2 is the statistical results of the growth of corn seeds on the 8th day of Example 1 under the stress of NaCl solutions of different concentrations. It can be seen from Table 2 that under the stress of NaCl, with the increase of NaCl concentration, the germination index of corn seeds generally shows a decreasing trend, but the various germination indicators are still at a relatively high level, with a germination rate of 92.00-98.00%, a germination potential of 88.00-95.00%, and a germination index of 22.50-30.60%. The corn seeds of Example 1 show excellent salt-alkali resistance.

[0060] Through the above limited experiments, the method of using silicone to improve the salt-alkali resistance of corn seeds in Example 1 of the present invention has significant application effect. By adding modified nano-hydroxyapatite and carboxymethyl cellulose simultaneously during the preparation of the silicone composite solution and spraying them on the surface of corn seeds, the salt-alkali resistance of corn seeds can be significantly improved to cope with the challenges brought by soil salinization, thereby improving agricultural production efficiency.

[0061] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the salt-alkali tolerance of corn seeds using organosilicon, characterized in that: The following steps are involved: S11. Seed pretreatment: Select plump corn seeds without disease spots and insects, rinse them with clean water 2-3 times, and then disinfect them with 75% alcohol for 30-60 seconds; S12. Pre-soaking: Soak the pre-treated corn seeds in purified water for 2-4 hours, stirring gently every 30 minutes. The volume ratio of corn seeds to purified water is 1:(1.5-2). After soaking, drain the moisture on the surface of the seeds. S13. Seed dressing: Place the pre-soaked corn seeds in a cantilever coating machine and spray the organosilicon composite solution by atomization. The mass ratio of corn seeds to organosilicon composite solution is 100:(1.5~3). The organosilicon composite solution is evenly added in 2~3 times. The speed is controlled at 150~200rpm, the blast temperature is 25~28℃, and the treatment time is 8~10min. S14. Drying: Place the corn seeds treated with seed dressing in an electric constant temperature air drying oven, set the air temperature to 25-30°C, treat for 1-1.5 hours, then take out and air dry naturally for 2-3 hours; S15. Post-ripening: Naturally pile the dried corn seeds at an ambient temperature of 20-25°C and use a light-shielding bag to avoid strong light exposure. After standing for 12-15 hours, store the obtained corn seeds away from light; The preparation method of the organosilicon composite solution comprises: S21. Slowly add carboxymethyl cellulose to purified water under stirring, set the heating temperature to 80-95°C, the stirring speed to 300-400 rpm, and stir for 0.5-1 h to obtain a carboxymethyl cellulose solution; S22. The modified nano-hydroxyapatite was slowly added to the carboxymethyl cellulose solution under stirring, and ultrasonic treatment was performed after stirring for 0.5 to 1 h. The intermittent mode was set to work for 2 min and stop for 1 min. The ultrasonic frequency was 40 to 50 kHz. The first mixed solution was obtained after ultrasonic treatment at room temperature for 0.5 to 1 h. S23. Slowly add the organosilicon solution to the first mixed solution under stirring, set the stirring temperature to 30-35°C, the stirring speed to 400-500 rpm, stir for 1-2 hours, transfer to a high-pressure homogenizer, set the pressure to 30-40 MPa, cycle 2-3 times, and filter through a 0.22 μm filter membrane to obtain an organosilicon composite solution.

2. The method for improving the salt-alkali tolerance of corn seeds by using organosilicon according to claim 1, characterized in that: The organic silicon solution is a compound of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane, wherein the weight ratio of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane is (20-25): (15-18): (10-12).

3. The method for improving the salt-alkali tolerance of corn seeds by using organosilicon according to claim 1, characterized in that: The carboxymethyl cellulose, modified nano-hydroxyapatite and organic silicon solution are contained in a weight ratio of (10-15):(2-4):(1-2).

4. The method for improving the salt-alkali tolerance of corn seeds by using organosilicon according to claim 1, characterized in that: The preparation method of the modified nano-hydroxyapatite comprises: S31. The hydroxyapatite was dispersed in purified water under stirring, and the acrylic acid monomer was slowly added after stirring for 0.5 to 1 h. After stirring for 1 to 2 h, ultrasonic treatment was performed. The intermittent mode was set to work for 2 min and stop for 1 min. The ultrasonic frequency was 40 to 50 kHz. After ultrasonic treatment at room temperature for 0.5 to 1 h, a second mixed solution was obtained. S32. Under nitrogen protection, the ammonium persulfate solution was added to the second mixed solution, the temperature was raised to 65-75°C, and the reaction was stirred for 4-6 hours to obtain a third mixed solution; S33. The third mixed solution is subjected to high-speed centrifugation at a rotation speed of 10000-12000 rpm for 10-15 min. The separated solid is washed alternately with purified water and anhydrous ethanol for 3 times and then vacuum dried at a drying temperature of 50-60° C. After drying for 12-14 h, the modified nano-hydroxyapatite is obtained and ground into powder for later use.

5. The method for improving the salt-alkali tolerance of corn seeds by using organosilicon according to claim 4, characterized in that: The modified nano-hydroxyapatite is obtained by grafting polyacrylic acid on the surface of hydroxyapatite and nano-crystallizing the surface of the hydroxyapatite. The particle size of the modified nano-hydroxyapatite is 45-60 nm and the specific surface area is 180-225 m 2 / g.

6. The method for improving the salt-alkali tolerance of corn seeds by using organosilicon according to claim 4, characterized in that: The mass ratio of the hydroxyapatite, acrylic acid monomer and ammonium persulfate solution is 1:(2-4):(0.2-0.4).

Citation Information

Patent Citations

  • Method for improving salt and alkaline-resistant property of corn germplasm resource seeds

    CN107172919A

  • GB1141796A

  • Method for pre-sowing treatment of barley seeds

    RU2618143C1

  • Organic-inorganic hybrid scaffolds with surface-immobilized nano-hydroxyapatite and preparation method thereof

    US20100160467A1

Cited By

  • Treating agent for promoting germination of corn seeds in saline-alkali environment and preparation method and application thereof

    CN121220494A